2015
DOI: 10.1021/acs.jctc.5b00304
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking the Bethe–Salpeter Formalism on a Standard Organic Molecular Set

Abstract: We perform benchmark calculations of the Bethe–Salpeter vertical excitation energies for the set of 28 molecules constituting the well-known Thiel’s set, complemented by a series of small molecules representative of the dye chemistry field. We show that Bethe–Salpeter calculations based on a molecular orbital energy spectrum obtained with non-self-consistent G0W0 calculations starting from semilocal DFT functionals dramatically underestimate the transition energies. Starting from the popular PBE0 hybrid functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
326
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 204 publications
(354 citation statements)
references
References 134 publications
28
326
0
Order By: Relevance
“…1. The optimal choice of gKS starting point, whether Hartree-Fock, a semi-local approximation, or a hybrid functional within density-functional theory (DFT), is not trivial for a given system and is currently an active area of research [41,39,42,38,43,44]. In any case, the wavefunctions and eigenvalues that result from the gKS calculation are used to produce the screened Coulomb interaction W which is an ingredient in both the GW approximation to the self-energy and in the BSE.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…1. The optimal choice of gKS starting point, whether Hartree-Fock, a semi-local approximation, or a hybrid functional within density-functional theory (DFT), is not trivial for a given system and is currently an active area of research [41,39,42,38,43,44]. In any case, the wavefunctions and eigenvalues that result from the gKS calculation are used to produce the screened Coulomb interaction W which is an ingredient in both the GW approximation to the self-energy and in the BSE.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Some authors [42,43,47] advocate for iterating further the GW equations by updating the eigenvalues in Eq. (1) to those from Eq.…”
Section: Gw Self-energymentioning
confidence: 99%
“…In several examples with atom-centered basis sets, the accuracy of selfconsistent GW is competitive with G 0 W 0 predictions using Hartree-Fock and hybrid functional mean-field starting points. [2][3][4][5]10,13,15,17,22,24,52,55 However, recent results for fully self-consistent GW on a plane-wave basis set report slightly larger errors. 19 Overall, self-consistent GW pushes the IPs upward compared to G 0 W 0 with a DFT starting point, and it shifts IPs slightly downward when using a Hartree-Fock starting point.…”
mentioning
confidence: 99%
“…3, we compare the first lowest optical singlet excitations predicted by TDSX with the revised best theoretical estimates for Thiel's test set, as obtained from reference literature values and quantum chemistry calculations, e.g., coupled cluster [88]. Thiel's test set consists of 28 molecules and was recently used for benchmarking state-of-the-art many-body perturbation theory techniques based on the Bethe-Salpeter-equation (BSE) and the GW approximation [89,90]. Jacquemin et al [91] found TDPBE0 (timedependent density functional calculations with the PBE0 functional) to be exceptionally accurate for this set, with the lowest mean absolute error compared to 28 exchange correlation functionals.…”
Section: Resultsmentioning
confidence: 99%
“…(10)], TDPBE0 and PBE0 with many-body perturbation theory corrections (BSE@G 0 W 0 @PBE0) TDPBE0 and BSE@G 0 W 0 @PBE0 are taken from Ref. [89].…”
Section: Resultsmentioning
confidence: 99%